Modulation of the peripheral immune system after low-dose radon spa therapy: Detailed longitudinal immune monitoring of patients within the RAD-ON01 study - Rühle, Paul-Friedrich; Wunderlich, Roland; Fournier, Claudia; Maier, Andreas; Klein, Gerhart; Fietkau, Rainer; Gaipl, Udo; Frey, Benjamin; Deloch, Lisa (Autoimmunity, 2017)
The pain-relieving effects of low-dose radon therapies on patients suffering from chronic painful inflammatory diseases have been described for centuries. Even though it has been suggested that low doses of radiation may attenuate chronic inflammation, the underlying mechanisms remain elusive. Thus, the RAD-ON01 study was initiated to examine the effects of radon spa therapy and its low doses of alpha radiation on the human immune system. In addition to an evaluation of pain parameters, blood was drawn from 100 patients suffering from chronic painful degenerative musculoskeletal diseases before as well as 6, 12, 18, and 30 weeks after the start of therapy. We verified significant long-term pain reduction for the majority of patients which was accompanied by modulations of the peripheral immune cells. Detailed immune monitoring was performed using a multicolor flow cytometry-based whole blood assay. After therapy, the major immune cells were only marginally affected. Nevertheless, a small but long-lasting increase in T cells and monocytes was observed. Moreover, neutrophils, eosinophils and, in particular, dendritic cells were temporarily modulated after therapy. Regarding the immune cell subsets, cytotoxic T and NK cells, in particular, were altered. However, the most prominent effects were identified in a strong reduction of the activation marker CD69 on T, B, and NK cells. Simultaneously, the percentage of HLA-DR+T cells was elevated after therapy. The RAD-ON01 study showed for the first time a modulation of the peripheral immune cells following standard radon spa therapy. These modulations are in line with attenuation of inflammation.
EVALuna2:32908